2022
DOI: 10.1177/01492063221094263
|View full text |Cite
|
Sign up to set email alerts
|

How and When Perceptions of Top Management Bottom-Line Mentality Inhibit Supervisors’ Servant Leadership Behavior

Abstract: Extending existing bottom-line mentality (BLM) perspectives, we provide a new theoretical account of how supervisors’ perceptions of top management BLM influence supervisors’ servant leadership (SL) behavior. Using role theory, we propose that these perceptions inhibit supervisors’ SL behavior by reducing their SL role conceptualization or the extent to which supervisors consider SL part of their work responsibility. Further, given that the process underlying the relationship between perceived top management B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…In fact, only four studies have examined factors that may propel leaders to adopt BLMs. In support of role modeling effects (Bandura, 1986), research has found that supervisors' perceptions of top management BLM positively influence the supervisor's own BLM (Babalola, Jordan, et al, 2022). Utilizing conservation of resources theory (Hobfoll, 1989), Rice and Reed (2021) argued that leaders' emotional exhaustion propels them to adopt BLMs to direct their attention toward "what matters most" as a way of coping with their lack of resources.…”
Section: An Overview Of Leader Blmmentioning
confidence: 99%
“…In fact, only four studies have examined factors that may propel leaders to adopt BLMs. In support of role modeling effects (Bandura, 1986), research has found that supervisors' perceptions of top management BLM positively influence the supervisor's own BLM (Babalola, Jordan, et al, 2022). Utilizing conservation of resources theory (Hobfoll, 1989), Rice and Reed (2021) argued that leaders' emotional exhaustion propels them to adopt BLMs to direct their attention toward "what matters most" as a way of coping with their lack of resources.…”
Section: An Overview Of Leader Blmmentioning
confidence: 99%
“…In line with previous studies on BLM ( Mawritz et al, 2017 ; Babalola et al, 2020a , 2022a , b ; Quade et al, 2021 ), and to improve the generalizability of our research findings ( Johns, 2006 ), we tested our hypotheses in two field studies on different populations. Data were collected from Pakistan and United States for Study 1 and Study 2, respectively.…”
Section: Overview Of Studiesmentioning
confidence: 87%
“…However, most previous studies have focused on the effects of constructive leadership on employee safety behaviors, and insufficient research has been conducted on destructive leadership [ 12 ]. As a practical but short-sighted management method, LBLM is also prevalent in an increasingly competitive business environment [ 22 , 79 ]. Given the harmful and prevalent nature of LBLM, this study further enriches the literature on safety behaviors by identifying LBLM as a hindering factor affecting employee safety behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study introduces Chinese traditionality as the boundary of the LBLM to influence subordinates’ safety behavior. Previous research has explored many individual differences that enhance or diminish the effects of LBLM, but attention to cultural value orientations remains insufficient [ 60 , 79 ]. Especially for workplaces like coal mines, which are relatively closed and have high power distance, individual cultural value orientations may play a more significant role [ 27 ].…”
Section: Discussionmentioning
confidence: 99%